Chaos Embedded Particle Swarm Optimization Technique for Solving Optimal Power Flow Problem - Daghan, Ismail Hakan; Gencoglu, Muhsin Tunay; Ozdemir, Mahmut Temel (Ieee, 2021)
This paper proposes chaos embedded particle swarm optimization, (CEPSO) to achieve optimal settings of the optimal power flow problem's (OPF) control variables. Various objective functions such as fuel cost minimization, voltage profile improvement, voltage stability enhancement, active and reactive power losses, are achieved through using the proposed algorithm. All objective functions are processed as single objectives in each case. The performance of the algorithm is tested on the IEEE standard 30 Bus system. The CEPSO's and PSO's results are compared with each other. As objective functions the fuel cost minimization, voltage profile improvement, reactive power loss minimization were first time processed by the proposed algorithm. The obtained result of the fuel cost objective function is compared with other algorithms' results.
18th International Multi-Conference on Systems, Signals & Devices (SSD) -- MAR 22-25, 2021 -- Monastir, TUNISIA
Keywords: optimal power flow; chaos; PSO; optimization